Total Protein Requirements of Beef Cattle I: Feed the Bugs First - Jeffrey N. Carter (EDIS, 2007)
AN167, a 2-page illustrated fact sheet by Jeffrey N. Carter, describes the role of beneficial microbes in the rumen of beef cattle which provide the primary source of protein for ruminant animals, microbial crude protein. Includes a line diagram depicting the path of dietary protein. Published by the UF Department of Animal Sciences, September 2006.